THE IMPACT OF DIGITAL DEVELOPMENT ON THE DUTIES AND AUTHORITIES OF NOTARIES IN INDONESIA - Windari Praptonowati Square (Jurnal Locus Delicti, 2025)
The development of digital technology has has brought changes significant in system service law, including in field notary as public officials who have authority For make authentic deeds faced with challenges adaptation to system Work digital- based research This aim For analyze implications development digital technology towards implementation duties and authorities notaries in Indonesia. The study focused on the use of sign hand electronics, services General Legal Administration (AHU Online), as well as digitalization document like Certificate Electronic Property Rights. Research results state that digital transformation in practice Notary Public is an inevitability that must be balanced with regulatory reform, increasing capacity technology notary, and strengthening protection law to document electronics. Recommendations main proposed is compilation regulations special about digital notary and strengthening infrastructure and training based technology in econotarial system national.